Enhancement of cleaner production assessment to identify workplace waste and hazard by value stream mapping - Ishak, Anuar (2018)
Throughout the years of industrialization, our environment has become severely polluted and contaminated. Sustainable management aims to recover, recycle, reuse and reduce wastes from industrial productions. To counter this problem, the Cleaner Production (CP) is a preventive, company-specific environmental protection initiatives, intended to minimize waste and emissions and maximize product output became an option to the put forward. In order to sustain their businesses, the companies used several methods, such as Lean Manufacturing (LM) as a powerful means employed to improve efficacy in the manufacturing field and get rid of muda (Japanese word for “waste”). By means of utilizing a set of tools to improve the manufacturing system for instance capable to eliminate the waste and hazard along the process flow. One of the influential lean visualizing tools known as Value Stream Mapping (VSM) have been used. But previous research has shown that the conventional VSM is difficult to apply to identify the workplace waste and hazard. Therefore, this study aims to investigate the practicality of the VSM with an extended approach introduced from United State Environmental Protection Agency (USEPA) and by the Department of Environment Malaysia was synchronized together known as Cleaner Production Value Stream Mapping (CPVSM) to assess wastes and hazard while promoting sustainable manufacturing. The findings of this study will help by implementing LM, many organizations relish cost reduction, process optimization, improve the quality of the product, improve the production process, reduce the pollution load to the environment and minimize hazards to the workers. To evaluate the CPVSM application, two case studies of local SME’s companies have been successfully implemented. Through this study, the author has investigated and recommended the CPVSM is one of the best, cheapest and holistic methods to identify waste and hazard in the manufacturing process. An extensive array of study outcomes also confirms that the waste and hazard has been easily identified in every possible source. Moreover, the CPVSM method also facilitates the focus on the relevant workstations on improving the Kaizen performance. In addition, this finding can be demonstrated through the previous Malaysian Green Industry Audit method with complicated reporting procedures, difficult to understand, especially for the Lean Practicioner (LP) and hence require substantial monetary funding to carry out Kaizen activities in the industry. In conclusion, the author can verify that through the synergy between CP method through CPVSM, a comprehensive form of discovery and classification of the waste and hazard can easily be implemented to help the industry to perform improvements. This CPVSM has been used to disclose the hot spots of wastes and potential hazards in the operation flows, applied to improve the current state of the operating conditions and to create a better future state process. This study aims to obtain a new testimony by using the CPVSM to identify the wastes and hazards to boost the benefits of economic, environmental controls and societal impact to the manufacturing sectors.